1999
DOI: 10.1007/s10434-999-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Severe Systemic Toxicity After Leakage-Controlled Isolated Limb Perfusion With Tumor Necrosis Factor-α and Melphalan

Abstract: Systemic toxicity after ILP with TNF-alpha is minimal and does not differ from that after ILP with melphalan alone when leakage is adequately controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…Application of ILP, with leakage below 5%, allows high local dosages of cytotoxic agents without the systemic side-effects (Benckhuijsen et al, 1988;Buckley et al, 1989;Vrouenraets et al, 1999). This means that local toxicity is the limiting factor.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%
“…Application of ILP, with leakage below 5%, allows high local dosages of cytotoxic agents without the systemic side-effects (Benckhuijsen et al, 1988;Buckley et al, 1989;Vrouenraets et al, 1999). This means that local toxicity is the limiting factor.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%
“…The perception that TNF-based ILP is a risky endeavor has been demonstrated to be false provided that leakage is monitored and well controlled. 13 But even in the event of significant leakage, we have demonstrated that with correct fluid management and postoperative care, patients do not develop major or life-threatening complications. 14 Therefore we do not think it is reasonable to consider age a limiting factor for patients to undergo a TNF-based ILP.…”
mentioning
confidence: 96%
“…[19][20][21] However, the use of TNF has been limited secondary to the serious toxicity of TNF in the systemic circulation. 22 Some investigators have devised strategies to mitigate the problems associated with the systemic release of soluble TNF through techniques such as hypothermic isolated limb perfusion of cells transduced in situ, 23,24 physically linking soluble TNF to the tumor-cell membrane, 25 using TNF in the form of a fusion molecule, 26,27 or by driving expression of TNF in transduced cells with weak, tissue-specific or radiation-inducible promoters. [27][28][29][30] In addition, others have used vectors encoding a truncated TNF that lacks the TACE cleavage site.…”
Section: Discussionmentioning
confidence: 99%